Waterborne polyurethane gel electrolyte, preparation method thereof and zinc ion battery
By using aqueous polyurethane gel electrolyte in zinc ion batteries, the stability and ion conduction ability of the electrolyte are enhanced by using the Hoffmeister effect, the problem of narrow electrochemical window of aqueous zinc ion batteries is solved, and a zinc ion battery with high energy density and high safety is achieved.
Patent Information
- Application Number
- CN202510372599.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-27
AI Technical Summary
The electrochemical window of aqueous zinc ion batteries is narrow, resulting in low energy density, limiting the development of high-voltage and high-specific energy zinc ion batteries.
After freezing and molding the aqueous polyurethane dispersion or anionically modified aqueous polyurethane dispersion, it is soaked in a zinc brine solution, and the Hoffmeister effect is used to form an aqueous polyurethane gel electrolyte, which enhances the stability and ion conduction ability of the electrolyte.
The electrochemical stability window of electrolytes is broadened, the voltage platform and energy density of zinc ion batteries is improved, while reducing preparation costs and improving safety.
Smart Images

Figure CN119890483A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of batteries, and in particular to an aqueous polyurethane gel electrolyte and a preparation method thereof, and a zinc ion battery. Background Art
[0002] Aqueous zinc-ion batteries have developed rapidly due to their advantages such as high safety, large theoretical capacity, low redox potential, and abundant zinc resources. However, aqueous zinc-ion batteries face the challenge of low energy density because the stable electrochemical window of their aqueous electrolytes is only 1.23V. Exceeding this window will trigger water decomposition reactions, reduce reversible capacity, and lead to side reactions. This limits the development of zinc-ion batteries, especially high-voltage and high-specific-energy zinc-ion batteries. Regulating the structure of aqueous electrolytes to improve the stability of aqueous electrolytes is the current main research direction, which is of great significance to the development of high-voltage zinc-ion batteries (such as flexible zinc-ion batteries).
[0003] At present, the main control strategies for broadening the electrochemical stability window of aqueous electrolytes are the high-concentration salt strategy (Water-in-salt) and the molecular crowding strategy, but these two strategies still have some problems. The high-concentration salt strategy can expand the electrochemical stability window, but it has problems such as strong corrosion, high toxicity, and high cost, which is not conducive to large-scale application. The molecular crowding strategy limits the activity of water molecules by adding organic matter to increase the operating voltage of the battery, but it faces problems such as reduced conductivity, high cost, and environmental pollution.
[0004] Therefore, there is an urgent need to develop a low-cost, high-safety method to broaden the electrochemical window of aqueous electrolytes and inhibit the electrolyte water decomposition reaction to achieve the preparation of high-energy zinc-ion batteries. Summary of the invention
[0005] Based on the above-mentioned deficiencies of the prior art, the object of the present invention is to provide an aqueous polyurethane gel electrolyte and a preparation method thereof and a zinc ion battery, aiming to solve the problem that the electrochemical window of the existing zinc ion battery using aqueous electrolyte is narrow.
[0006] The technical solution of the present invention is as follows: A first aspect of the present invention provides a method for preparing an aqueous polyurethane gel electrolyte, comprising the following steps: Providing a first dispersion, wherein the first dispersion is an aqueous polyurethane dispersion or an anion-modified aqueous polyurethane dispersion; the anion-modified aqueous polyurethane dispersion is obtained by reacting an aqueous polyurethane dispersion with an anionic hydrophilic monomer having an amino group; After the first dispersion is freeze-formed, it is immersed in a zinc salt aqueous solution to induce the Hofmeister effect, thereby obtaining the aqueous polyurethane gel electrolyte.
[0007] Optionally, the method for preparing the aqueous polyurethane dispersion comprises the following steps: Mixing polyol, diisocyanate, catalyst and organic solvent, and reacting to obtain a first reaction liquid, wherein the first reaction liquid contains a polyurethane prepolymer; Adding a hydrophilic chain extender with a carboxyl group to the first reaction liquid, and after reaction, obtaining a second reaction liquid, wherein the second reaction liquid contains a polyurethane prepolymer with a carboxyl group; adding a neutralizing agent to the second reaction liquid, and obtaining a polyurethane prepolymer with a hydrophilic group after reaction; The polyurethane prepolymer with hydrophilic groups is dispersed in water to obtain the aqueous polyurethane dispersion.
[0008] Optionally, the preparation method of the anion-modified aqueous polyurethane dispersion comprises the following steps: Mixing polyol, diisocyanate, catalyst and organic solvent, and reacting to obtain a first reaction liquid, wherein the first reaction liquid contains a polyurethane prepolymer; Adding a hydrophilic chain extender with a carboxyl group to the first reaction liquid, and after reaction, obtaining a second reaction liquid, wherein the second reaction liquid contains a polyurethane prepolymer with a carboxyl group; adding a neutralizing agent to the second reaction liquid, and obtaining a polyurethane prepolymer with a hydrophilic group after reaction; Dispersing the polyurethane prepolymer with hydrophilic groups into water to obtain the aqueous polyurethane dispersion; The aqueous polyurethane dispersion is mixed with an anionic hydrophilic monomer having an amino group, and after reaction, the anionic modified aqueous polyurethane dispersion is obtained.
[0009] Optionally, the polyol includes at least one of polyethylene glycol, polycaprolactone diol, polyethylene glycol dimethacrylate and diethylene glycol; The diisocyanate comprises at least one of isophorone diisocyanate, hexamethylene diisocyanate, lysine diisocyanate and diphenylmethane diisocyanate; The catalyst comprises at least one of dibutyltin dilaurate, dimethyltin dihydroxyacetate, N,N-dimethylcyclohexylamine and triethyl phosphate; The hydrophilic chain extender with a carboxyl group includes at least one of 2,2-dimethylol propionic acid and 2,2-dimethylol butyric acid; The neutralizing agent includes at least one of triethanolamine and NaOH.
[0010] Optionally, the anionic hydrophilic monomer having an amino group includes at least one of carbamate, aminosulfonate and methyl carbamate.
[0011] Optionally, the zinc salt includes at least one of zinc sulfate, zinc perchlorate, zinc trifluoromethanesulfonate and zinc fluoroborate; and the concentration of the zinc salt in the zinc salt aqueous solution is 0.05-1.0 mol / L.
[0012] Optionally, the mass ratio of the polyol, the diisocyanate, the catalyst, the hydrophilic chain extender with a carboxyl group and the neutralizer is 1: (1.4-1.85): 0.01: (0.4-0.8): (0.4-0.8); In the aqueous polyurethane dispersion, the mass ratio of the polyurethane prepolymer with hydrophilic groups to water is (1-3):1.
[0013] Optionally, the mass ratio of the aqueous polyurethane dispersion to the anionic hydrophilic monomer with an amino group is (1-3):1.
[0014] In a second aspect of the present invention, an aqueous polyurethane gel electrolyte is provided, wherein the aqueous polyurethane gel electrolyte is prepared by the preparation method of the present invention as described above.
[0015] According to a third aspect of the present invention, a zinc ion battery is provided, wherein the zinc ion battery comprises a positive electrode sheet, a negative electrode sheet, and an electrolyte located between the positive electrode sheet and the negative electrode sheet, and the electrolyte is the aqueous polyurethane gel electrolyte as described above in the embodiment of the present invention.
[0016] Beneficial effects: The present invention freezes and forms an aqueous polyurethane dispersion or an anion-modified aqueous polyurethane dispersion, and then immerses the dispersion in a zinc salt aqueous solution to form an aqueous polyurethane gel electrolyte. At the same time, the Hofmeister effect is used to form a strong hydrogen bond between the aqueous polyurethane hydrophilic groups, zinc salt anions and water molecules in the aqueous polyurethane gel electrolyte, thereby inducing the free water molecules in the aqueous polyurethane gel electrolyte to transform into bound water, thereby preparing an aqueous polyurethane gel electrolyte with a wide voltage window and high ionic conductivity, thereby enabling the zinc ion battery to obtain a higher voltage platform and energy density. The preparation method provided by the present invention has low cost and high safety. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 Schematic diagram of the preparation mechanism of the aqueous polyurethane gel electrolyte in an embodiment of the present invention.
[0018] Figure 2 Schematic diagrams of zinc ion deposition on the surfaces of different electrolytes, where (a) is a traditional hydrogel electrolyte and (b) is an aqueous polyurethane gel electrolyte in an embodiment of the present invention.
[0019] Figure 3 This is a physical picture of the aqueous polyurethane gel electrolyte prepared in Example 1 of the present invention.
[0020] Figure 4 This is a linear sweep voltammetry curve of the aqueous polyurethane gel electrolyte prepared in Example 1 of the present invention.
[0021] Figure 5 This is a cyclic voltammetry curve of the flexible zinc ion battery prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0022] The present invention provides an aqueous polyurethane gel electrolyte and a preparation method thereof and a zinc ion battery. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0023] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0024] An embodiment of the present invention provides a method for preparing an aqueous polyurethane gel electrolyte, which comprises the following steps: S1. providing a first dispersion, wherein the first dispersion is an aqueous polyurethane dispersion or an anion-modified aqueous polyurethane dispersion; the anion-modified aqueous polyurethane dispersion is obtained by reacting an aqueous polyurethane dispersion with an anionic hydrophilic monomer having an amino group; S2. After freeze-forming the first dispersion, immersing the dispersion in a zinc salt aqueous solution to induce a Hofmeister effect, thereby obtaining the aqueous polyurethane gel electrolyte.
[0025] like Figure 1 As shown, in the embodiment of the present invention, after the aqueous polyurethane dispersion or the anion-modified aqueous polyurethane dispersion is freeze-formed, it is immersed in a zinc salt aqueous solution to induce the Hofmeister effect. During the reaction, when the zinc salt anions in the zinc salt aqueous solution come into contact with the amphiphilic molecular chains with a protein-like structure in the aqueous polyurethane, the aggregation state of the aqueous polyurethane molecular chains can be increased, and its solubility in water can be reduced, thereby causing salting out to obtain an aqueous polyurethane gel electrolyte. At the same time, strong hydrogen bonds are formed between the hydrophilic groups of the polyurethane molecular chains, the zinc salt anions and the water molecules to form an isolated "hydrophilic cage", which can induce the aqueous polyurethane gel electrolyte (i.e. Figure 1The free water molecules inside the gel matrix in the electrolyte are transformed into bound water, thereby inhibiting the water decomposition reaction and widening the electrochemical stability window of the electrolyte. In addition, the aqueous polyurethane gel electrolyte obtained based on the Hofmeister effect contains a large amount of zinc salt anions, which can form ion channels, promote the transmission and uniform deposition of zinc ions, and thus have a higher ionic conductivity. The Hofmeister effect can cause the hydrophobic molecular groups of the amphiphilic polymer chain to migrate and aggregate to the external interface, thereby improving the surface adhesion of the aqueous polyurethane gel electrolyte, which is beneficial to improving the interface stability between the electrolyte and the electrode of the zinc ion battery. Therefore, the preparation method provided by the present invention can be used to prepare an aqueous polyurethane gel electrolyte with a wide voltage window (i.e., an electrochemical stability window), high ionic conductivity and high stability, thereby enabling the zinc ion battery to obtain a higher voltage platform and energy density. The preparation method provided by the present invention is low in cost and high in safety.
[0026] In addition, because the Hofmeister effect is through the formation of strong hydrogen bonds between zinc salt anions, water molecules and hydrophilic groups of polyurethane molecular chains, Figure 2 As shown in (b) in Figure 2, introducing anionic functional groups into the polymer molecular chain (i.e., using anionic modified waterborne polyurethane) can optimize the hydrophilicity of the waterborne polyurethane gel electrolyte and regulate the local concentration of bound water. More importantly, Figure 2 As shown in (a), the conventional hydrogel electrolyte has low ionic conductivity and is prone to zinc dendrite problems. However, in the present invention, Figure 2 As shown in (b), the anions introduced into the anion-modified waterborne polyurethane can complex with zinc ions to form ion channels, promote zinc ion transport through electrostatic forces, and induce uniform deposition of zinc ions.
[0027] In step S1, in some embodiments, the method for preparing the aqueous polyurethane dispersion comprises the following steps: S11, mixing a polyol, a diisocyanate, a catalyst and an organic solvent, and reacting to obtain a first reaction liquid, wherein the first reaction liquid contains a polyurethane prepolymer; S12, adding a hydrophilic chain extender having a carboxyl group to the first reaction liquid, and after reaction, obtaining a second reaction liquid, wherein the second reaction liquid contains a polyurethane prepolymer having a carboxyl group; S13, adding a neutralizing agent to the second reaction liquid, and after reaction, obtaining a polyurethane prepolymer with a hydrophilic group; S14, dispersing the polyurethane prepolymer with hydrophilic groups into water to obtain the aqueous polyurethane dispersion.
[0028] In some embodiments, the method for preparing the anion-modified aqueous polyurethane dispersion includes the above steps S11 to S14, and further includes the following steps: S15, mixing the aqueous polyurethane dispersion with an anionic hydrophilic monomer having an amino group, and after reaction, obtaining the anionic modified aqueous polyurethane dispersion.
[0029] In step S11, the hydroxyl group (-OH) in the polyol and the isocyanate group (-NCO) in the diisocyanate undergo a polyaddition reaction to generate a carbamate group, that is, a polyurethane group (-NH-COO-), thereby forming a polyurethane prepolymer.
[0030] The reaction formula is: R-NCO+R'-OH→R-NH-COO-R'; Among them: R-NCO represents a diisocyanate molecule, wherein R is an organic group of the diisocyanate; R'-OH represents a polyol molecule, wherein R' is an organic group in the polyol.
[0031] In step S12, a hydrophilic chain extender with a carboxyl group (such as 2,2-dihydroxymethylpropionic acid) is subjected to a chain extension reaction with the end groups at both ends of the polyurethane prepolymer molecular chain, namely, the isocyanate group (-NCO) (after the reaction in step S11, -NCO has basically reacted to form R-NH-COO-R', but the end groups at both ends of the obtained polyurethane prepolymer molecular chain are still -NCO groups), forming a polyurethane prepolymer with a carboxyl group (the end groups at both ends are still -NCO).
[0032] In step S13, a neutralizing agent (such as triethanolamine, NaOH) neutralizes the carboxyl groups in the polyurethane prepolymer with carboxyl groups to generate a waterborne polyurethane prepolymer with hydrophilic groups (the terminal groups at both ends of the prepolymer are still -NCO).
[0033] In step S15, the amino group in the anionic hydrophilic monomer with an amino group directly reacts with the terminal isocyanate group in the waterborne polyurethane molecular chain to generate a urea group (-NH-CO-NH-) for end-capping to obtain an anionic modified waterborne polyurethane prepolymer.
[0034] Exemplarily, the amino group directly reacts with the isocyanate group to form a urea linkage, and the reaction process is as follows: R''-NCO+R'''-NH 2 →R''-NH-CO-NH-R'''; Among them, R''-NCO represents an organic molecule containing an isocyanate group; R'''-NH 2 Represents organic molecules containing amino groups.
[0035] The resulting product R''-NH-CO-NH-R''' is a urea compound containing a urea group (-NH-CO-NH-).
[0036] In step S11, in some embodiments, the reaction temperature is 60-80°C, and the reaction time is 12-24 hours. For example, the reaction temperature can be 60°C, 65°C, 70°C, 75°C or 80°C, and the reaction time can be 12 hours, 15 hours, 18 hours, 20 hours, 22 hours or 24 hours.
[0037] In step S11, in some embodiments, the polyol includes at least one of polyethylene glycol, polycaprolactone diol, polyethylene glycol dimethacrylate and diethylene glycol, but is not limited thereto.
[0038] In some embodiments, the diisocyanate includes at least one of isophorone diisocyanate, hexamethylene diisocyanate, lysine diisocyanate, and diphenylmethane diisocyanate, but is not limited thereto.
[0039] In some embodiments, the catalyst includes at least one of dibutyltin dilaurate, dimethyltin dihydroxyacetate, N,N-dimethylcyclohexylamine, and triethyl phosphate, but is not limited thereto.
[0040] In some embodiments, the organic solvent includes at least one of acetone and methyl ethyl ketone, but is not limited thereto.
[0041] In step S12, in some embodiments, the hydrophilic chain extender with a carboxyl group includes at least one of 2,2-dimethylol propionic acid and 2,2-dimethylol butyric acid, but is not limited thereto.
[0042] In step S12, in some embodiments, the reaction temperature is 60-80° C., and the reaction time is 2-5 hours. For example, the reaction temperature can be 60° C., 65° C., 70° C., 75° C., or 80° C., and the reaction time can be 2 hours, 3 hours, 4 hours, or 5 hours.
[0043] In step S13, in some embodiments, the neutralizing agent includes at least one of triethanolamine (TEA) and NaOH, but is not limited thereto.
[0044] In step S13, in some embodiments, the reaction temperature is 60-80° C., and the reaction time is 2-5 hours. For example, the reaction temperature can be 60° C., 65° C., 70° C., 75° C., or 80° C., and the reaction time can be 2 hours, 3 hours, 4 hours, or 5 hours.
[0045] In step S14, in some embodiments, the anionic hydrophilic monomer having an amino group includes at least one of carbamate (such as sodium carbamate), aminosulfonate (such as sodium aminosulfonate) and methyl carbamate (sodium methyl carbamate), but is not limited thereto.
[0046] In some specific embodiments, the anionic hydrophilic monomer with an amino group includes at least one of 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt, [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonatepropyl)ammonium hydroxide, 2-acrylamido-2-methylpropanesulfonic acid, and vinylbenzenesulfonate ammonium, but is not limited thereto.
[0047] In step S14, in some embodiments, the reaction temperature is 60-80° C., and the reaction time is 2-5 hours. For example, the reaction temperature can be 60° C., 65° C., 70° C., 75° C., or 80° C., and the reaction time can be 2 hours, 3 hours, 4 hours, or 5 hours.
[0048] In steps S11 and S12, in some embodiments, the mass ratio of the polyol, the diisocyanate, the catalyst, the hydrophilic chain extender with a carboxyl group and the neutralizer is 1: (1.4-1.85): 0.01: (0.4-0.8): (0.4-0.8), for example, it can be 1: 1.4: 0.01: 0.4: 0.4, 1: 1.45: 0.01: 0.4: 0.4, 1: 1.65: 0.01: 0.6: 0.6 or 1: 1.85: 0.01: 0.8: 0.8, etc.
[0049] In step S14, in some embodiments, in the aqueous polyurethane dispersion, the mass ratio of the polyurethane prepolymer with hydrophilic groups to water is (1-3): 1, for example, it can be 1: 1, 2: 1 or 3: 1, etc.
[0050] In step S15, in some embodiments, the mass ratio of the aqueous polyurethane dispersion to the anionic hydrophilic monomer having an amino group is (1-3): 1, for example, 1: 1, 2: 1 or 3: 1, etc.
[0051] In step S15, in some embodiments, the reaction temperature is 40-60° C., and the reaction time is 1-3 hours. For example, the reaction temperature can be 40° C., 45° C., 50° C., 55° C., or 60° C., and the reaction time can be 1 hour, 2 hours, or 3 hours.
[0052] In step S2, in some embodiments, the zinc salt includes at least one of zinc sulfate, zinc perchlorate, zinc trifluoromethanesulfonate and zinc fluoroborate, but is not limited thereto.
[0053] In some embodiments, the concentration of the zinc salt in the zinc salt aqueous solution is 0.05-1.0 mol / L, for example, 0.05 mol / L, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L or 1.0 mol / L, etc. The greater the concentration of the zinc salt in the zinc salt aqueous solution, the stronger the mechanical strength of the aqueous polyurethane gel electrolyte, because the zinc salt anions are coupled with water molecules and hydrophilic groups of the aqueous polyurethane molecular chains through hydrogen bonds, which increases the aggregation of the polyurethane molecular chains and thus increases the mechanical strength. Different zinc salt concentrations in the zinc salt aqueous solution will produce aqueous polyurethane gel electrolytes with different water contents.
[0054] In step S2, the first dispersion can be placed in a -50°C environment for freeze molding to obtain an aqueous polyurethane matrix, and the aqueous polyurethane matrix is immersed in a zinc salt aqueous solution for a period of time, so that the zinc salt aqueous solution penetrates into the aqueous polyurethane matrix to induce the Hofmeister effect. When the zinc salt anions contact the amphiphilic molecular chains in the aqueous polyurethane, strong hydrogen bonds are formed between the zinc salt anions, water molecules and the hydrophilic groups of the polyurethane molecular chains, so that the molecular chains are cross-linked until the polyurethane is cured and forms an elastic gel material, and the surface moisture is wiped off to obtain the aqueous polyurethane gel electrolyte.
[0055] An embodiment of the present invention further provides an aqueous polyurethane gel electrolyte, wherein the aqueous polyurethane gel electrolyte is prepared by the preparation method of the present invention as described above.
[0056] An embodiment of the present invention further provides a zinc ion battery, wherein the zinc ion battery comprises a positive electrode sheet, a negative electrode sheet, and an electrolyte located between the positive electrode sheet and the negative electrode sheet, and the electrolyte is the aqueous polyurethane gel electrolyte as described above in the embodiment of the present invention.
[0057] The zinc ion battery provided by the embodiment of the present invention has a higher voltage platform and energy density. Of course, in the present invention, the positive electrode plate, the aqueous polyurethane gel electrolyte and the negative electrode plate can be arranged and then packaged by an aluminum-plastic film or the like.
[0058] In some embodiments, the positive electrode plate includes a positive electrode current collector and a positive electrode dressing layer located on the positive electrode current collector, the positive electrode current collector includes one of carbon cloth and graphite paper, and the positive electrode dressing layer includes a positive electrode active material (such as graphite), a conductive agent (conductive carbon black) and a binder (such as polyvinylidene fluoride, abbreviated as PVDF).
[0059] In some embodiments, the method for preparing the positive electrode sheet comprises the following steps: providing a positive electrode current collector; The positive electrode active material, the conductive agent and the binder are mixed in a preset ratio (e.g., a mass ratio of 8:1:1), and then an organic solvent (e.g., N-methylpyrrolidone) is added and mixed to obtain a positive electrode slurry; The positive electrode slurry is coated on the positive electrode current collector and dried to obtain the positive electrode sheet.
[0060] In some embodiments, the negative electrode plate is zinc foil or the like.
[0061] The present invention will be further described below by means of specific examples.
[0062] Example 1 This embodiment provides a method for preparing an aqueous polyurethane gel electrolyte, comprising the following steps: 30 g of polyethylene glycol, 42 g of isophorone diisocyanate, 0.3 g of dibutyltin dilaurate and 100 g of acetone were mixed and stirred, and reacted at 80° C. in a nitrogen atmosphere for 12 hours to obtain a first reaction liquid, wherein the first reaction liquid contained a polyurethane prepolymer; 12 g of 2,2-dimethylol propionic acid was added to the first reaction liquid, and the mixture was reacted at 80° C. for 2 h to obtain a second reaction liquid; 12 g of TEA was added to the second reaction liquid, and reacted at 80° C. for 2 h to obtain a polyurethane prepolymer with a hydrophilic group; Dispersing 30 g of a polyurethane prepolymer having a hydrophilic group into 30 g of water to obtain an aqueous polyurethane dispersion; 50 g of 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt and 50 g of the aqueous polyurethane dispersion were mixed and reacted at 60° C. for 2 h to obtain an anion-modified aqueous polyurethane dispersion; The anion-modified waterborne polyurethane dispersion is placed in a -50°C low-temperature box for freezing and molding to obtain a waterborne polyurethane matrix; The concentration is 0.05 mol·L -1 The waterborne polyurethane matrix was immersed in 0.05 mol·L zinc sulfate aqueous solution. -1The aqueous solution of zinc sulfate was immersed in the aqueous polyurethane for 1 h to allow the aqueous polyurethane to penetrate into the matrix and induce the Hofmeister effect until the aqueous polyurethane was solidified and formed into an elastic gel material. The surface moisture was wiped off to obtain an aqueous polyurethane gel electrolyte (such as Figure 3 as shown).
[0063] At the same time, the concentration of 0.1 mol·L -1 , 0.5mol·L -1 and 1.0 mol·L -1 The above waterborne polyurethane matrix was immersed in 0.1 mol·L zinc sulfate aqueous solution. -1 , 0.5mol·L -1 and 1.0 mol L -1 The zinc sulfate aqueous solution was placed in the aqueous polyurethane matrix for 1 h to induce the Hofmeister effect until the aqueous polyurethane was cured and formed into an elastic gel material. The surface moisture was wiped off to obtain three other aqueous polyurethane gel electrolytes, such as Figure 3 shown.
[0064] The linear sweep voltammetry curves of the above four aqueous polyurethane gel electrolytes were tested by an electrochemical workstation, and their electrochemical stability windows were measured. Specifically, a zinc sheet was used as a counter electrode and a reference electrode, an inert stainless steel sheet was used as a working electrode, and an aqueous polyurethane gel electrolyte was placed between the zinc sheet and the stainless steel sheet to assemble a button cell. The linear sweep voltammetry mode was set on the electrochemical workstation to test the electrochemical stability window of the button cell (i.e., the aqueous polyurethane gel electrolyte).
[0065] The results are as follows Figure 4 The results show that with the increase of zinc salt concentration, the voltage stability window of aqueous polyurethane gel electrolyte gradually widens and can reach up to 2.6 V (relative to Zn / Zn 2+ The standard electrode potential of the redox couple is 2.6 V, and the concentration of zinc salt used to prepare the aqueous polyurethane gel electrolyte is 1.0 mol·L -1 ), and the zinc salt concentration is 0.05 mol·L -1 The obtained aqueous polyurethane gel electrolyte was broadened by about 0.6V.
[0066] This embodiment also provides a method for preparing a flexible zinc ion battery, wherein an aqueous polyurethane gel electrolyte (composed of 1.0 mol·L -1 The flexible zinc ion battery is an aqueous secondary zinc ion battery system. The preparation of the flexible zinc ion battery includes the following steps: (1) Preparation of flexible positive electrode sheet A flexible conductive carbon cloth with a thickness of 0.2 mm is used as a positive electrode current collector, graphite is used as a positive electrode material, conductive carbon black is used as a conductive agent, and water-soluble PVDF is used as a binder. Graphite, water-soluble PVDF and conductive carbon black are mixed in a mass ratio of 8:1:1, and N-methylpyrrolidone is added and fully ground to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on the flexible conductive carbon cloth and placed in an oven to dry to obtain a flexible positive electrode sheet.
[0067] (2) Battery assembly A zinc sheet with a thickness of 0.2 mm was used as the flexible negative electrode sheet, and a nickel tab (specification: thickness × width × length 0.1 mm × 2 mm × 20 mm) was respectively pasted on the flexible positive electrode sheet and the flexible negative electrode sheet using white adhesive tape; A flexible negative electrode sheet, an aqueous polyurethane gel electrolyte and a flexible positive electrode sheet are assembled in order to form a battery cell, which is then packaged using an aluminum-plastic film through a vacuum heat sealer to obtain a flexible zinc-ion battery.
[0068] The cyclic voltammetry curve of the flexible zinc-ion battery was tested by an electrochemical workstation, and its voltage platform was obtained. Figure 5 As shown, its voltage platform is about 2.06V.
[0069] Example 2 This embodiment provides a method for preparing an aqueous polyurethane gel electrolyte, comprising the following steps: 30 g of polyethylene glycol, 49.5 g of isophorone diisocyanate, 0.3 g of dimethyltin dihydroxyacetate and 100 g of acetone were mixed and stirred, and reacted at 80° C. in a nitrogen atmosphere for 12 hours to obtain a first reaction liquid, wherein the first reaction liquid contained a polyurethane prepolymer; 18 g of 2,2-dimethylol propionic acid was added to the first reaction liquid, and the mixture was reacted at 80° C. for 3 h to obtain a second reaction liquid; 18 g of TEA was added to the second reaction liquid, and reacted at 80° C. for 3 h to obtain a polyurethane prepolymer with a hydrophilic group; Dispersing 30 g of a polyurethane prepolymer having a hydrophilic group into 20 g of water to obtain an aqueous polyurethane dispersion; 10 g of 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt and 20 g of the aqueous polyurethane dispersion were mixed and reacted at 60° C. for 3 h to obtain an anion-modified aqueous polyurethane dispersion; The anion-modified waterborne polyurethane dispersion is placed in a -50°C low-temperature box for freezing and molding to obtain a waterborne polyurethane matrix; The concentration is 0.1 mol·L -1 The aqueous polyurethane matrix was immersed in a 0.1 mol·L zinc sulfate aqueous solution.-1 The aqueous solution of zinc sulfate was immersed in the aqueous polyurethane for 2 h to allow the aqueous polyurethane to penetrate into the matrix and induce the Hofmeister effect until the aqueous polyurethane was cured to form an elastic gel material. The surface moisture was wiped off to obtain an aqueous polyurethane gel electrolyte.
[0070] This embodiment also provides a method for preparing a flexible zinc ion battery, which is different from Embodiment 1 only in that the aqueous polyurethane gel electrolyte prepared in Embodiment 2 is used.
[0071] Example 3 This embodiment provides a method for preparing an aqueous polyurethane gel electrolyte, comprising the following steps: 30 g of polyethylene glycol, 54 g of isophorone diisocyanate, 0.3 g of N,N-dimethylcyclohexylamine and 100 g of acetone were mixed and stirred, and reacted at 80° C. in a nitrogen atmosphere for 12 hours to obtain a first reaction liquid, wherein the first reaction liquid contained a polyurethane prepolymer; 24 g of 2,2-dimethylol propionic acid was added to the first reaction liquid, and the mixture was reacted at 80° C. for 4 h to obtain a second reaction liquid; 24 g of TEA was added to the second reaction liquid, and reacted at 80° C. for 4 h to obtain a polyurethane prepolymer with a hydrophilic group; Dispersing 30 g of a polyurethane prepolymer having a hydrophilic group into 10 g of water to obtain an aqueous polyurethane dispersion; 10 g of 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt and 30 g of the aqueous polyurethane dispersion were mixed and reacted at 60° C. for 3 h to obtain an anion-modified aqueous polyurethane dispersion; The anion-modified waterborne polyurethane dispersion is placed in a -50°C low-temperature box for freezing and molding to obtain a waterborne polyurethane matrix; The concentration is 1.0 mol·L -1 The waterborne polyurethane matrix was immersed in 1.0 mol·L zinc sulfate aqueous solution. -1 The aqueous solution of zinc sulfate was immersed in the aqueous polyurethane for 0.5 h to allow the aqueous polyurethane to penetrate into the matrix and induce the Hofmeister effect until the aqueous polyurethane was cured to form an elastic gel material. The surface moisture was wiped off to obtain an aqueous polyurethane gel electrolyte.
[0072] This embodiment also provides a method for preparing a flexible zinc ion battery, which is different from Embodiment 1 only in that the aqueous polyurethane gel electrolyte prepared in Embodiment 3 is used.
[0073] In summary, the present invention provides an aqueous polyurethane gel electrolyte and a preparation method thereof and a zinc ion battery. The present invention freezes and forms an aqueous polyurethane dispersion or an anion-modified aqueous polyurethane dispersion, and then immerses the aqueous polyurethane dispersion in a zinc salt aqueous solution to form a hydrogel matrix. At the same time, the Hofmeister effect is used to form a strong hydrogen bond between the hydrophilic groups of the aqueous polyurethane, the zinc salt anions and the water molecules in the hydrogel matrix, and the free water molecules in the hydrogel matrix are induced to transform into bound water, thereby preparing an aqueous polyurethane gel electrolyte with a wide voltage window and high ionic conductivity, thereby enabling the zinc ion battery to obtain a higher voltage platform and energy density. The method provided by the present invention is low in cost and high in safety.
[0074] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A method for preparing an aqueous polyurethane gel electrolyte, characterized in that: The steps include: Providing a first dispersion, wherein the first dispersion is an aqueous polyurethane dispersion or an anion-modified aqueous polyurethane dispersion; the anion-modified aqueous polyurethane dispersion is obtained by reacting an aqueous polyurethane dispersion with an anionic hydrophilic monomer having an amino group; After the first dispersion is freeze-formed, it is immersed in a zinc salt aqueous solution to induce the Hofmeister effect, thereby obtaining the aqueous polyurethane gel electrolyte.
2. The method for preparing an aqueous polyurethane gel electrolyte according to claim 1, characterized in that: The preparation method of the aqueous polyurethane dispersion comprises the following steps: Mixing polyol, diisocyanate, catalyst and organic solvent, and reacting to obtain a first reaction liquid, wherein the first reaction liquid contains a polyurethane prepolymer; Adding a hydrophilic chain extender with a carboxyl group to the first reaction liquid, and after reaction, obtaining a second reaction liquid, wherein the second reaction liquid contains a polyurethane prepolymer with a carboxyl group; adding a neutralizing agent to the second reaction liquid, and obtaining a polyurethane prepolymer with a hydrophilic group after reaction; The polyurethane prepolymer with hydrophilic groups is dispersed in water to obtain the aqueous polyurethane dispersion.
3. The method for preparing an aqueous polyurethane gel electrolyte according to claim 1, characterized in that: The preparation method of the anion-modified aqueous polyurethane dispersion comprises the following steps: Mixing polyol, diisocyanate, catalyst and organic solvent, and reacting to obtain a first reaction liquid, wherein the first reaction liquid contains a polyurethane prepolymer; Adding a hydrophilic chain extender with a carboxyl group to the first reaction liquid, and after reaction, obtaining a second reaction liquid, wherein the second reaction liquid contains a polyurethane prepolymer with a carboxyl group; adding a neutralizing agent to the second reaction liquid, and obtaining a polyurethane prepolymer with a hydrophilic group after reaction; Dispersing the polyurethane prepolymer with hydrophilic groups into water to obtain the aqueous polyurethane dispersion; The aqueous polyurethane dispersion is mixed with an anionic hydrophilic monomer having an amino group, and after reaction, the anionic modified aqueous polyurethane dispersion is obtained.
4. The method for preparing an aqueous polyurethane gel electrolyte according to claim 2 or 3, characterized in that: The polyol comprises at least one of polyethylene glycol, polycaprolactone diol, polyethylene glycol dimethacrylate and diethylene glycol; The diisocyanate comprises at least one of isophorone diisocyanate, hexamethylene diisocyanate, lysine diisocyanate and diphenylmethane diisocyanate; The catalyst comprises at least one of dibutyltin dilaurate, dimethyltin dihydroxyacetate, N,N-dimethylcyclohexylamine and triethyl phosphate; The hydrophilic chain extender with a carboxyl group includes at least one of 2,2-dimethylol propionic acid and 2,2-dimethylol butyric acid; The neutralizing agent includes at least one of triethanolamine and NaOH.
5. The method for preparing an aqueous polyurethane gel electrolyte according to claim 1 or 3, characterized in that: The anionic hydrophilic monomer having an amino group includes at least one of carbamate, aminosulfonate and methyl carbamate.
6. The method for preparing an aqueous polyurethane gel electrolyte according to claim 1, characterized in that: The zinc salt includes at least one of zinc sulfate, zinc perchlorate, zinc trifluoromethanesulfonate and zinc fluoroborate; and the concentration of the zinc salt in the zinc salt aqueous solution is 0.05-1.0 mol / L.
7. The method for preparing an aqueous polyurethane gel electrolyte according to claim 2 or 3, characterized in that: The mass ratio of polyol, diisocyanate, catalyst, hydrophilic chain extender with carboxyl group and neutralizer is 1: (1.4~1.85): 0.01 :(0.4~0.8):(0.4~0.8); In the aqueous polyurethane dispersion, the mass ratio of the polyurethane prepolymer with hydrophilic groups to water is (1-3):
1.
8. The method for preparing an aqueous polyurethane gel electrolyte according to claim 3, characterized in that: The mass ratio of the aqueous polyurethane dispersion to the anionic hydrophilic monomer with an amino group is (1-3):
1.
9. An aqueous polyurethane gel electrolyte, characterized in that: The aqueous polyurethane gel electrolyte is prepared by the preparation method according to any one of claims 1 to 8.
10. A zinc ion battery, characterized in that: The zinc ion battery comprises a positive electrode sheet, a negative electrode sheet and an electrolyte located between the positive electrode sheet and the negative electrode sheet, and the electrolyte is the aqueous polyurethane gel electrolyte according to claim 9.
Citation Information
Patent Citations
Preparation method of novel anionic-nonionic waterborne polyurethane polymer electrolyte
CN112920365A
Polyethyleneimine / polyurethane hydrogel electrolyte as well as preparation method and application thereof
CN114058030A
Dendritic crystal-free zinc-based battery composite electrode and preparation method and application thereof
CN118136977A
Hydrogel electrolyte, preparation method thereof and thermal battery
CN118970221A
Asymmetric hydrogel electrolyte and preparation method thereof
CN119340507A